Babes in tomorrowland : Walt Disney and the making of the American child, 1930-1960 - Sammond, Nicholas, 1960- (E-Duke books scholarly collection., 2005)
Examines the place of Disney in the changing construction of childhood in mid-twentieth-centru America.